Angiotensin II‐induced natriuresis is attenuated in knockout mice lacking the receptors for tumor necrosis factor‐α. Issue 15 (2nd August 2021) - Majid, Dewan S. A.; Castillo, Alexander
Abstract: Intravenous infusion of relatively higher doses of angiotensin II (AngII) elicits natriuresis as opposed to its usual anti‐natruretic response. As AngII can induce tumor necrosis factor‐α (TNFα) production which elicits natriuresis via its action on TNFα receptor type 1 (TNFR1), we hypothesize that the concomitant release of TNFα contributes to the natriuretic response to AngII. Responses to AngII infusion (1 ng min −1 g −1 for 75 min, iv) were evaluated in anesthetized knockout (KO) mice lacking TNFR1 ( n = 6) and TNFR2 (TNFα receptor type 2; n = 6) and compared these responses with those in wild type (WT; n = 6) mice. Arterial pressure (AP) was recorded from a cannula placed in the carotid artery. Renal blood flow (RBF) and glomerular filtration rate (GFR) were measured by PAH and inulin clearances, respectively. Urine was collected from a catheter placed in the bladder. AngII caused similar increases ( p < 0.05 vs basal values) in AP (WT, 37 ± 5%; TNFR1KO, 35 ± 4%; TNFR2KO, 30 ± 4%) and decreases ( p < 0.05) in RBF (WT, −39 ± 5%; TNFR1KO, −28 ± 6%; TNFR2KO, −31 ± 4%) without significant changes in GFR (WT, −17 ± 7%; TNFR1KO, −18 ± 7%; TNFR2KO, −12 ± 7%). However, despite similar changes in AP and renal hemodynamics, AngII induced increases ( p < 0.05) in urinary sodium excretion in WT (3916 ± 942%) were less in the KO strains, more or less in TNFR1KO (473 ± 170%) than in TNFR2KO (1176 ± 168%). These data indicate that TNF‐α receptors, particularly TNFR1 are involved in the natriuretic response that occur during acute infusion of AngII and thus, plays a protective role in preventing excessive salt retention at clinical conditions associated with elevated AngII level. Abstract : Short summary of the study: The present study examined the role of concomitant TNF‐α formation in regulating renal responses to angiotensin II (AngII) by evaluating its effects in mice lacking TNF receptor type 1 (TNFR1KO) and type 2 (TNFR2KO) and compared to that in WT mice. The results showed that TNFR1 activation is involved in the natriuresis induced by AngII and suggest a protective role of TNFR1 in preventing excessive salt retention during elevated AngII level.